Answer:
I think it is (x^2+9) x (x-1) x (x+1)
Step-by-step explanation:
(not sure if right but had a go)
Answer:
Step-by-step explanation:
Below the sea level should be mentioned by negative value
So, It is = - 4.5
9514 1404 393
Answer:
Step-by-step explanation:
Let g and b represent the numbers of candy canes the girl and boy have, respectively.
g -1 = b +1 . . . . . . girl gives to boy, they're equal
g +1 = 2(b -1) . . . . boy gives to girl; she has double
Adding 1 to the first equation gives an expression for g that can be substituted into the second equation.
g = b +2
(b +2) +1 = 2b -2
5 = b . . . . . . . . . . add 2-b, simplify
g = 5+2 = 7 . . . . . find g
The girl has 7 candy canes; the boy has 5.
The simplified expression of
is ![\frac{9}{x^9}](https://tex.z-dn.net/?f=%5Cfrac%7B9%7D%7Bx%5E9%7D)
<h3>How to simplify the expression?</h3>
The expression is given as:
![\sqrt{\frac{162x^9}{2x^{27}}}](https://tex.z-dn.net/?f=%5Csqrt%7B%5Cfrac%7B162x%5E9%7D%7B2x%5E%7B27%7D%7D%7D)
Divide 162 and 2 by 2
![\sqrt{\frac{81x^9}{x^{27}}}](https://tex.z-dn.net/?f=%5Csqrt%7B%5Cfrac%7B81x%5E9%7D%7Bx%5E%7B27%7D%7D%7D)
Take the square root of 81
![9\sqrt{\frac{x^9}{x^{27}}}](https://tex.z-dn.net/?f=9%5Csqrt%7B%5Cfrac%7Bx%5E9%7D%7Bx%5E%7B27%7D%7D%7D)
Apply the quotient rule of indices
![9\sqrt{\frac{1}{x^{27-9}}}](https://tex.z-dn.net/?f=9%5Csqrt%7B%5Cfrac%7B1%7D%7Bx%5E%7B27-9%7D%7D%7D)
Evaluate the difference
![9\sqrt{\frac{1}{x^{18}}}](https://tex.z-dn.net/?f=9%5Csqrt%7B%5Cfrac%7B1%7D%7Bx%5E%7B18%7D%7D%7D)
Take the square root of x^18
![\frac{9}{x^9}](https://tex.z-dn.net/?f=%5Cfrac%7B9%7D%7Bx%5E9%7D)
Hence, the simplified expression of
is ![\frac{9}{x^9}](https://tex.z-dn.net/?f=%5Cfrac%7B9%7D%7Bx%5E9%7D)
Read more about expressions at:
brainly.com/question/723406
#SPJ1
Answer:
c may be the correct one l am 55% sure